A sustained dual drug delivery system for proliferative vitreoretinopathy. (1st January 2020) - Xiao, Ying; Choi, Kyung Seek; Warther, David; Huffman, Kristyn; Landeros, Stephanie; Freeman, William R.; Sailor, Michael J.; Cheng, Lingyun
Abstract: Proliferative vitreoretinopathy (PVR) is a significant threat for vision recovery from retinal detachment or ocular trauma. Currently, no approved pharmacological intervention to prevent PVR. Daunorubicin (DNR) and dexamethasone (DEX) were sequentially loaded into oxidized porous silicon (pSiO2 ) particles by covalent conjugation. The DNR + DEX-loaded particles, and control particles loaded with DNR only and DEX only were incubated with RPE-populated collagen for daily gel surface quantitation. Toxicity was monitored by ophthalmic examinations and histological evaluation 21 days after injection. At 3rd week following intravitreal injection, a localized retinal detachment (RD) was created by subretinal injection of Healon in all pretreated eyes in addition to 3 non-interventional control eyes. 10 µg of bromodeoxyuridine (BrdU) was injected into the vitreous 4 h before sacrifice on day 3 after RD induction. Retinal sections were stained for glial fibrillary green protein (GFAP) and BrdU to identify activated glial cells and retinal cell proliferation. The studies demonstrated that all three pSiO2 particle types were well tolerated in vivo. DNR alone and DNR + DEX combination formulations demonstrated equally strong suppression on gel contraction (least square mean area of the gel: control = 1.71 vs. 30DNR = 1.85 or 30/40Dual = 1.83, p  < .05). Eyes pretreated with pSiO2 −DNR + DEX exhibited the least GFAP activation (least square mean intensity mm −2 : Dual = 4.03, DNR = 7.76, Dex = 16.23, control = 29.11, p  < .05) and BrdU expression (Mean number of BrdU positive cells per mm of retina: Dual = 2.77, DNR = 4.58, Dex = 4.01, control = 6.16, p  < .05). The synergistic effect of a sustained release pSiO2 −DNR/DEX showed promise for the prevention of PVR development while reducing the necessary therapeutic concentration of each drug.